THE WORD FREQUENCY LIST OF STUDENTS’ MINI THESES COLLECTION - Paulina Erawati Paramita (IKIP PGRI Pontianak, 2018)
The study of vocabulary is an effective way to help the learners to increase their vocabulary in the target language. Word frequency list helps learners determine the most useful words to study. To systematically study vocabulary, learners may use those words to help them to write a better mini-theses enriched with huge vocabulary knowledge, and then apply the appropriate words on their writings. The collection of twenty-one students’ mini-theses from English study program was processed by TextStat to list the frequency word vocabulary. Finally, 1000 frequently used words were presented to see the words selection used by the students in writing their mini-theses. Most of the words found in mini-theses are functional words. This corpus of 1000 words can be utilized as a reference for the students to improve their vocabulary and writing.Keywords: words, vocabulary, frequency, corpus, textstat